Structure of the complex of cytochrome c with cardiolipin in non-polar environment - Vladimirov, G. K.; Vikulina, Anna S.; Volodkin, Dmitry; Vladimirov, Yu A. A. (Chemistry and physics of lipids, 2018)
The complex of mitochondrial protein cytochrome c (CytC) with anionic phospholipid cardiolipin (CL) plays a crucial role in the initiation of apoptosis by catalyzing lipid peroxidation in mitochondrial membranes. In our previous papers, we found that CytC and CL mixed in millimolar concentrations form a sediment showing microcrystals composed of nanospheres (Cyt-CL) of 11–12 and 8 nm in diameter. The hypothesis was proposed that Cyt-CL, having hydrophobic shell, may appear inside the membrane lipid bilayer in mitochondria and peroxidase membrane phospholipids so initiating the apoptotic cascade. In this work, Cyt-CL complex dissolved in chloroform or hexane was investigated as a model of the complex in mitochondrial membranes. We used dynamic light scattering method to measure the size of the particles. The analysis of particles size distribution of Cyt-CL in chloroform allows to reveal three dominant diameters of 12.1 ± 1.4, 7.8 ± 1.0, and 4.7 ± 0.7 nm. The first two values are closed to those, earlier obtained with small-angle X-ray scattering method in Cyt-CL microcrystals, 11.1 ± 1.0 and 8.0 ± 0.7 nm. CL extracted in chloroform-methanol forms a real solution of particles with diameter of 0.7 ± 0.1 nm. In methanol-water phase, CL and CL + CytC mixture form particles of 83.7 ± 9.8 and 71.3 ± 11.6 nm, respectively. Apparently, cardiolipin in 50% methanol forms single-layer liposomes regardless of the presence of CytC in the medium. Partial unfolding of CytC in the complex was evidenced by (a) appearance of fluorescence of tyrosine and tryptophan residues and (b) disappearance of the absorption band at 699 nm due to breakdown of heme iron – methionine bond > F⋯S(Met80). In hydrophobic solvent Cyt-CL exhibited quasi-lipoperoxidase and lipoxygenase activity as was shown in kinetic measurements of chemiluminescence enhanced by coumarin C-525, a selective sensitizer of chemiluminescence, associated with reactions of lipid peroxyl radicals. Our data in this model system do not contradict the hypothesis (Vladimirov, Y.A. et al. Biochemistry (Mosc) 78, 1086–1097) that nanospheres of Cyt-CL complex, embedded into the lipid phase of mitochondrial membrane, catalyze lipid peroxidation, thereby initiating apoptosis.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Cardiolipin; Chemiluminescence; Cytochrome c; Dynamic light scattering